2013
DOI: 10.1186/1752-1947-7-163
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of pneumatosis cystoides intestinalis after steroid tapering in a patient with bronchial asthma: a case report

Abstract: IntroductionWe report the case of a patient who was diagnosed as having pneumatosis cystoides intestinalis while being treated with prednisolone for bronchial asthma. Even before we had experienced a case of this, the relationship between pneumatosis cystoides intestinalis and prednisolone was unclear. In this case, pneumatosis cystoides intestinalis was improved with the reduction of prednisolone, and therefore we thought a direct relationship between pneumatosis cystoides intestinalis and prednisolone might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 14 publications
(11 reference statements)
0
22
0
Order By: Relevance
“…Bowel infarction was shown by abdominal X-ray, and the patient underwent exploration and a double ileostomy. In the third case, a 25-year-old woman with asthma developed PI after high-dose prednisolone 6 . She reported chronic abdominal pain, but her symptom resolved after tapering of the prednisolone.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Bowel infarction was shown by abdominal X-ray, and the patient underwent exploration and a double ileostomy. In the third case, a 25-year-old woman with asthma developed PI after high-dose prednisolone 6 . She reported chronic abdominal pain, but her symptom resolved after tapering of the prednisolone.…”
Section: Discussionmentioning
confidence: 92%
“…The primary type, which is not associated with other diseases, accounts for about 15% of the cases, and the secondary type accounts for the remaining 85% of the cases 2 . More than 58 diseases are associated with the secondary type including gastrointestinal, pulmonary, connective tissue, and hematological diseases 1 , 6 . The clinical manifestations and prognosis of PI are diverse and reflect those of the associated disease 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with cancer usually receive immunosuppressive or steroid therapies that may induce lymphoid depletion in Peyer’s patches, which impairs the gastrointestinal defence mechanism, reduces peristalsis and compromises the intestinal wall integrity. 7 , 8 Some authors have observed an association between steroids and PI, 7 , 13 with an improvement of PI after tapering steroids, 7 but there is no statistical association between PI and the amount of steroids or chemotherapeutic agents (cisplatin, fluorouracil, gemcitabine, bevacizumab). 13 Some authors have suggested that PI can be considered benign when confined to the colon and in the absence of “worrisome” CT scan findings such as bowel dilatation, bowel wall thickening, mesenteric stranding, ascites and portomesenteric venous gas.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 15% of PI cases are primary or idiopathic and 85% are secondary which can be resulted from a wide spectrum of GI or systemic diseases, although primary PI is benign and asymptomatic, but abdominal pain is the most frequent symptom of secondary PI6 and some of the secondary PI causes are life threatening 1–3 5–8…”
Section: Introductionmentioning
confidence: 99%